2011
DOI: 10.3155/1047-3289.61.6.640
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Model Performance between AERMOD and AUSTAL2000

Abstract: In this study the performance of the American Meteorological Society and U.S. Environmental Protection Agency Regulatory Model (AERMOD), a Gaussian plume model, is compared in five test cases with the German Dispersion Model according to the Technical Instructions on Air Quality Control (Ausbreitungsmodell gemäbeta der Technischen Anleitung zur Reinhaltung der Luft) (AUSTAL2000), a Lagrangian model. The test cases include different source types, rural and urban conditions, flat and complex terrain. The predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Not only can it sort the pollutant concentrations, but it can make three types of contour maps, including the annual average, the daily average and the hourly value, using the predicted results. Langner and Klemm's experiments have shown that the predictions of the model are closer to field observations [7]. In cases with complex and urban terrain, AERMOD is the stronger model compared with AUSTAL2000.…”
mentioning
confidence: 76%
“…Not only can it sort the pollutant concentrations, but it can make three types of contour maps, including the annual average, the daily average and the hourly value, using the predicted results. Langner and Klemm's experiments have shown that the predictions of the model are closer to field observations [7]. In cases with complex and urban terrain, AERMOD is the stronger model compared with AUSTAL2000.…”
mentioning
confidence: 76%
“…Lagrangian plume models are wellestablished regulatory tools for environmental impact assessments. Examples of regulatory models applied widely also within the research community are the Italian dispersion models SPRAY [Tinarelli et al, 1994;Gariazzo et al, 2004] and MicroSpray [Anfossi et al, 2010], the German regulatory model AUSTAL2000 [Janicke et al, 2004;Langner and Klemm, 2011], the UK Met Office model NAME [Ryall and Maryon, 1998;Jones et al, 2007], or the Gaussian puff model CALPUFF [Scire et al, 2000]. The NAME model is a particularly versatile model used operationally for environmental emergency response and volcanic ash cloud modeling as well as for various research applications [Jones et al, 2007].…”
Section: Plume Modelsmentioning
confidence: 99%
“…The results of Table 4 are framed within the acceptance criteria of dispersion models of air quality. To determine the reliability of the model, the criteria was used in previous studies [29,32,33] The NMSE, indicator of variance, is ˂ 0.5 for the weekly average of all stations, indicating that the observed concentrations and the estimated are agreed. The FB was positive for all environmental receptors and is within the accepted range, indicating that the estimated results are close to the values observed.…”
Section: Air Dispersion Modelmentioning
confidence: 99%